Android-Based Fast-Track Scoreboard Application Development in Assessing Academic Writing - Hariadi, Try; Suwandi, Sarwiji; Slamet, St. Y.; Sumarwati, Sumarwati (Opción, 2019)
This research aims to describe the lecturers’ and undergraduates’ state, need, development, and effectiveness. R&D covers several stages starting from exploration, development, and product testing. Research finding, the academic writing quality is far from what it is supposed to be, still conventional, and needs improvement. The draft is validated, identified, and implemented. The data in both control class (0.7704t (1.67) with α=0.05. tt Thus, android-based fast-track scoreboard application is more effective than con- ventional application.